Anisakis simplex (s.l.) resistance to the action of gastric enzymes depends upon previous treatments applied to infected fish mince and affects antigen release. (22nd January 2021) - Sánchez‐Alonso, Isabel; Carballeda‐Sangiao, Noelia; Rodríguez, Santiago; Tejada, Margarita; Navas, Alfonso; Arcos, Susana C; González‐Muñoz, Miguel; Careche, Mercedes
Abstract: Background: Freezing is considered the most suitable technological treatment to avoid Anisakis infection from eating raw or undercooked fish but modifications of their cuticles upon freezing may reduce their resistance to gastric fluids, provoking a greater release of allergens. This work aimed to study the relationship between freezing‐induced modifications of Anisakis simplex s.l ., antigen recognition, and resistance to oral and gastric digestion in spiked fish mince. Results: (i) Differences between non‐treated larvae and larvae that survived freezing / thawing were studied in terms of respiratory capacity, survival in simulated gastric fluid (SGF), recognition of antigens and allergens. (ii) Untreated (i.e. chilled) mince containing live larvae, mince frozen at two freezing rates, with a negative (uninfected) mince and a positive mince (infected with broken larvae) as controls, were subjected to the oral and gastric phases of a simulated digestion process. Anisakis able to survive freezing showed lower resistance to gastric fluid (i.e. faster mortality as compared to controls). Untreated larvae released significantly more antigens than freeze‐surviving larvae but only after 96 h in SGF. In treatments rendering complete larvae mortality, the highest loss of larvae integrity was found upon fast freezing. There was a positive correlation between antigen release and the number of ruptures of larvae after the oral digestion phase, whereas a more complex trend was observed after oral plus gastric digestion phases. Conclusion: These results suggest a new factor to consider for sensitized patients and suggest that the numbers of L3 should be reduced before industrial freezing to minimize risk. © 2020 Society of Chemical Industry